Viabilidad de suspender la pena privativa de libertad impuesta en sentencia de segunda instancia y la posibilidad de recurrir en la apelación en caso de negativa ante la Corte Nacional de Justicia - Pico Almeida, Edwin Alex (2022)
In this investigation named: FEASIBILITY OF SUSPENDING THE DEPRIVATION OF FREEDOM IMPOSED IN A SECOND INSTANCE SENTENCE AND THE POSSIBILITY OF APPEALING IN THE APPEAL IN CASE OF NEGATIVE BEFORE THE NATIONAL COURT OF JUSTICE. The purpose of this research project is to analyze the figure of the conditional suspension of the sentence, and examine the different possibilities of the granting or refusal of the aforementioned criminal subrogation, this figure is established in the second chapter, third section, fifth paragraph, from article 630 to 633 of the Comprehensive Criminal Organic Code. What is intended to demonstrate are two possibilities: The first is to benefit from the suspension of the sentence, when he is sentenced for the first time, and the possibility of appealing in case the benefit is denied and, the second possibility, is to request the suspension of the penalty for new facts, if the benefit is denied, it is still appealable. This proposal would prevent several rights recognized by the Magna Carta from being violated, such as the right to petition, appeal and double consent, in addition to the analyzes that were developed, there are two precedents of the Constitutional Court, where it is granted to the convicted for the first time in any procedural resource the possibility of appeal, guaranteeing the right to double consent, with which suspension of sentence could be requested when a person is sentenced for the first time based on mutatis mutandis.,,,,,,,,